Penggunaan Google Form Sebagai Instrumen Assesmen Kebutuhan Siswa - Nurul Hidayatul Ulum; Agus Basuki; Eva Imania Eliasa (Journal of Public Policy Analys, 2023)
Assessment within the framework of guidance and counselling serves as a basis for planning guidance and counseling programmes according to needs, enabling the achievement of the goals of guidance and counseling services through the suitability of the program and description of the counselee's condition and environmental conditions. This study uses a qualitative approach. Researchers used researchers as the main instrument, conducted purposive sampling of questionnaire data, used inductive/qualitative data collection and analysis techniques, and the results emphasized meaning rather than generalizations. It can be concluded that the main purpose of implementing the assessment instrument is to collect data. Data can be defined in various scientific contexts as a collection of information or information about objects or non-objects. For example, intelligence data can be defined as a collection of numbers, measurements, quantities, descriptions, or classifications of a person's intelligence. Personal data can also be defined as a collection of numbers, measurements, amounts, descriptions or classifications of a person's intelligence. In this case the data in question is student data obtained using internet-based media, namely Google Form. Overall, this discussion shows that using Google Forms as a student needs assessment tool has many advantages, such as ease of use and efficiency, as well as the ability to collect and analyze data in real time. However, keep in mind that factors related to internet access can be a barrier to this use. In such a situation, an alternative solution may be needed as described by the author in the previous paragraph. With the existence of a google form with the various conveniences offered by google, it is the author's hope that guidance and counseling teachers can utilize this media to make their work easier to be more efficient and adapt to the latest technological developments.